Establishment Trimester-Specific Reference Intervals of Anticoagulation and Fibrinolysis Indicators in Healthy Pregnant Women in Beijing, China - Linzi Miao MS; Xiao Sun MD; Zijing Zhu MS; Yuanyuan Li MS; Yao Lu MS; Ran You MS; Chenxue Qu MD (Clinical and Applied Thrombosis/Hemostasis)
Objective Continuously tracking and monitoring the changes in indicators of anticoagulation and fibrinolysis in healthy pregnant women during different pregnancy periods, to establish trimester-specific reference intervals. Methods A total of 200 healthy pregnant women registered in Peking University First Hospital were enrolled. Venous blood samples were collected at different pregnancy periods, and thirteen related anticoagulation and fibrinolysis indicators were tested. The impact of pregnancy periods on these indicators were analyzed, and corresponding reference intervals were established. Results Significant differences were observed among the non-pregnant group and the first trimester(6–8weeks), second trimester(24–28weeks), and third trimester(36–38weeks) groups for antithrombin (AT), protein S activity (PS Ac), free protein S (FPS), protein C (PC), D-Dimer, fibrin/fibrinogen degradation products (FDP), plasmin inhibitor (PI), plasminogen (PLG), von Willebrand factor activity (vWF:Ac), von Willebrand factor antigen (vWF:Ag), lupus anticoagulant. AT, PS Ac, and FPS showed a downward trend with increasing gestational period. PI was significantly increased in the first trimester. PLG and vWF:Ag was higher in the second trimester and the third trimester. vWF:Ac, D-Dimer and FDP showed an continuously upward trend with increasing gestational period; the normalized SCT ratio (SCT TR)was significantly lower in the third trimester; the normalized dRVVT ratio (dRVVT TR)was significantly higher in the second and third trimester. Conclusion This study established reference intervals for thirteen anticoagulant and fibrinolytic indicators in healthy pregnant women in Beijing, China. Additionally, pregnancy periods affect the test results of anticoagulant and fibrinolytic indicators in pregnant women, and the reference intervals should be established separately according to pregnancy periods.